Barium isotopes reveal role of ocean circulation on barium cycling in the Atlantic. (1st May 2017) - Bates, Stephanie L.; Hendry, Katharine R.; Pryer, Helena V.; Kinsley, Christopher W.; Pyle, Kimberley M.; Woodward, E. Malcolm S.; Horner, Tristan J.
Abstract: We diagnose the relative influences of local-scale biogeochemical cycling and regional-scale ocean circulation on Atlantic barium cycling by analysing four new depth profiles of dissolved Ba concentrations and isotope compositions from the South and tropical North Atlantic. These new profiles exhibit systematic vertical, zonal and meridional variations that reflect the influence of both local-scale barite cycling and large-scale ocean circulation. Epipelagic decoupling of dissolved Ba and Si reported previously in the tropics is also found to be associated with significant Ba isotope heterogeneity. As such, we contend that this decoupling originates from the depth segregation of opal and barite formation but is exacerbated by weak vertical mixing. Zonal influence from isotopically-'heavy' water masses in the western North Atlantic evidence the advective inflow of Ba-depleted Upper Labrador Sea Water, which is not seen in the eastern basin or the South Atlantic. Meridional variations in Atlantic Ba isotope systematics below 2000 m appear entirely controlled by conservative mixing. Using an inverse isotopic mixing model, we calculate the Ba isotope composition of the Ba-poor northern end-member as +0.45 ‰ and the Ba-rich southern end-member +0.26 ‰, relative to NIST SRM 3104a. The near-conservative behaviour of Ba below 2000 m indicates that Ba isotopes can serve as an independent tracer of the provenance of northern- versus southern-sourced water masses in the deep Atlantic Ocean. This finding may prove useful in palaeoceanographic studies, should appropriate sedimentary archives be identified, and offers new insights into the processes that cycle Ba in seawater.